ECONOMIC ISSUES OF DEVELOPMENT OF THE FOREST RESOURCES OF A TERRITORY - I. S. Zinov'eva (Russian Journal of Economics and Law)
The article is devoted to the study of economic issues of development of the forest resources of a territory. The author reveals the low development of the normative-legal base of the country and numerous ecological problems of forest utilization which directly result from the drawbacks in organizational-economic management of the country's forest resources. The author pays attention to the non-observation of the principles of efficient management of forests, the high cost of regeneration felling, and the financial aspects of the low efficiency of the Russian forest resources development. Measures to solve the problems are proposed.